From MOF‐74‐Zn to Triazolate‐Directed Nonsymmetric Assembly of Chiral Zn6@Zn6 Clusters. Issue 45 (12th July 2019) - Yang, Huajun; Le, James; Dinh, Andy; Zhao, Xiang; Chen, Xitong; Peng, Fang; Feng, Pingyun; Bu, Xianhui
Abstract: The creation of new cluster building blocks, as well as new ligand coordination modes, are among the most effective ways to develop new framework materials. Yet, large and chiral clusters are both difficult to create and relatively few. Here, by studying the competing coordination of different azolates against carboxylate and combined carboxylate/phenolate, it is shown that the impact of azolates in the MOF‐74 synthesis system differs dramatically, leading to the synthesis of MOF‐74, UTSA‐74, and CPM‐72 for 2‐methylimidazole, 1, 2, 4‐triazole, and 1, 2, 3‐triazole, respectively. The new CPM‐72 contains a novel chiral Zn12 triazolate cluster, which features a trigonal‐prismatic Zn6 core inside an octahedral Zn6 shell. In contrast with MOF‐74 with fully deprotonated and symmetrically bonded 2, 5‐dihydroxyterephthalic acid (H4 DOBDC), H4 DOBDC adopts an unusual nonsymmetric bonding mode in CPM‐72 (carboxylate only at one end and carboxylate/phenolate at the other), resulting in a highly porous and intrinsically chiral 3D framework. The nonsymmetric bonding mode by H4 DOBDC, apparently dictated by the chiral Zn12 cluster, can be replicated with 2‐hydroxyterephthalic acid (H3 OBDC), leading to the synthesis of porous isoreticular CPM‐73. Abstract : Asymmetry born out of symmetry : Mediated by triazolate, the achiral MOF‐74 structure turns into a chiral framework built on large and chiral core–shell‐type Zn6 @Zn6 cluster with unusual low‐symmetric bonding mode by H4 DOBDC ligand.